Implementation of Image Data Security Using the AES-256 Algorithm in the Work Accident Recording System - Dzulfiqar Alang Setiawan; Bambang Agus Herlambang; Ramadhan Renaldy (Universitas Bina Sarana Informatika, 2026)
This study aims to implement an image data security mechanism in a web-based work accident recording system in an industrial environment by applying the Advanced Encryption Standard (AES) 256-bit cryptographic algorithm in Cipher Block Chaining (CBC) mode. The problem faced is the lack of an adequate protection mechanism for sensitive work accident photo files so that they have the potential to be accessed, copied, or modified by unauthorized parties. This study uses the Software-Oriented Prototyping method which allows system development to be carried out iteratively based on user needs and evaluation results at each development stage. The encryption process is carried out when the image file is uploaded into the system by generating a random Initialization Vector (IV) of 16 bytes, then the image data is encrypted using the AES-256-CBC algorithm and stored in ciphertext form with the file extension .enc. The decryption process is carried out when the file will be displayed again using the appropriate secret key and IV without storing the file in plaintext form on the server. The test results show that the encryption process has an average execution time of around 0.002–0.008 seconds, while the decryption process takes around 0.00004–0.001 seconds. In addition, the size of the encrypted file relatively follows the size of the original image file with an additional size of around 16–32 bytes due to the padding process and the use of initialization vectors. The results of the study indicate that the application of the AES-256-CBC algorithm is able to maintain the confidentiality and integrity of image data without having a significant impact on system performance. Thus, the developed system can improve the security of digital file storage and support a more structured, secure, and efficient management of work accident data.